TI_GERICHTE 14.2011.89 vom 28. Juni 2011 , Reclamo contro dichiarazione di fallimento. Solvibilitâ non resa verosimile - TI Tribunale d'appello (2011)
Reclamo contro dichiarazione di fallimento. Solvibilitâ non resa verosimile